Generating creative solutions to address over-the-counter medication safety in older adults using invisible design - Ashley O Morris; Maria E Berbakov; Aaron M Gilson; Corey A Lester; Jamie A Stone; Michelle A Chui (Human Factors in Healthcare, 2023)
Background: Participatory design (PD) is commonly used in human factors to develop and design interventions. Invisible design is a useful tool that can be applied in PD for generating intervention ideas with stakeholders, to solve complex problems without requiring end-users to be able to entirely articulate the “problem.” This study utilized invisible design to build a community-pharmacy intervention for older adults, to improve their over-the-counter medication safety. In the U.S., half of adults ages 65 and above (older adults) use over-the-counter medications (OTCs) unsafely. The purpose of this paper is to describe invisible design and highlight its value when designing system-level interventions. Methods: Invisible design is a scenario-based approach that allows participants to brainstorm solutions to an unseen problem. In this study, invisible design was used to elicit stakeholder feedback to inform a new pharmacy-based intervention designed to reduce OTC medication misuse. A series of video scenarios were developed to help stakeholders imagine solutions to the identified patient safety gaps in older adult medication selection and pharmacy interactions. Results: Stakeholders used the invisible design videos to imagine 52 solutions on how to address OTC medication safety in pharmacies. The solutions were grouped into three goals: (1) Facilitating Patient Autonomy, (2) Facilitating a Pharmacist-Patient Encounter, and (3) Facilitating Informed Pharmacist Recommendations. Many of these generated solutions were adopted as features of a pharmacy-based intervention, the Senior Section. Conclusions: Invisible design successfully led to the brainstorming of innovative solutions by key stakeholders and could be used to develop future interventions outside of the field of pharmacy.